2005
DOI: 10.1080/09297040590911167
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Characteristics of Children With the 22q11 Deletion Syndrome: A Descriptive Analysis

Abstract: Previous reports of cognitive functioning in children with the 22q11 Deletion Syndrome have reported marked variability in IQ and achievement subtest scores. Studies have begun to explore neuropsychological function in 22q11 DS however results are inconsistent and the profile incomplete. We assessed 40 children ages 5-12 with 22q11 DS. Consistent with past results, visual-spatial memory was significantly lower than verbal memory. Differentially lowered scores were found only in visual attention, working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 25 publications
(23 reference statements)
3
84
2
Order By: Relevance
“…However, cognitive and neuropsychological testing of this study group revealed extremely broad subtest score scatter for each child tested on both IQ and neuropsychological batteries, invalidating the calculation and use of composite IQ scores for this group (13). Selection of a single subtest score would have been arbitrary, and we did not attempt to conceptualize an IQ estimation for these subjects.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cognitive and neuropsychological testing of this study group revealed extremely broad subtest score scatter for each child tested on both IQ and neuropsychological batteries, invalidating the calculation and use of composite IQ scores for this group (13). Selection of a single subtest score would have been arbitrary, and we did not attempt to conceptualize an IQ estimation for these subjects.…”
Section: Limitationsmentioning
confidence: 99%
“…Marked deficits have been found in visual location memory and working memory (9,10), selective and executive visual attention (11)(12)(13), and sensorimotor functioning (13), perhaps suggesting impairment in the prefrontal cortex and in pathways linking prefrontal and subcortical regions. However, neuropsychological tests alone can lack functional specificity.…”
mentioning
confidence: 99%
“…Some of the cognitive abnormalities observed in patients with 22q11DS are thought to originate in the prefrontal cortex and hippocampus including deficits in attention, working memory, executive function and short-term verbal memory [74][75][76] . Approximately 25% of 22q11DS patients suffer from schizophrenia or schizoaf- [77][78][79] .…”
Section: Q11mentioning
confidence: 99%
“…Neuropsychological test results suggested that the primary deficits among children with 22q11DS were likely to include attention, executive function, [6][7][8] and motor behavior, 7 three functional domains that are linked in the brain. Performance of children with 22q11DS on tasks that tapped more specific brain pathways within these relatively broad functional regions have helped to substantiate these initial findings.…”
mentioning
confidence: 99%